New-onset Thyroid Eye Disease after COVID-19 Vaccination in a Radioactive Iodine-Treated Graves’ Disease Patient: A Case Report and Literature Review - Teoh, Jamie Hong Im; Mustafa, Norlaila; Wahab, Norasyikin (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Autoimmunity associated with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has been well-described as the mechanism of development of thyroid dysfunction following Coronavirus Disease 19 (COVID-19) infection and SARS-CoV-2 vaccination. However, the occurrence of thyroid eye disease (TED) after SARS-CoV-2 vaccination is scarcely described. The postulated mechanisms include immune reactivation, molecular mimicry and the autoimmune/inflammatory syndrome induced by adjuvants (ASIA). We report a case of new-onset TED after receiving the SARSCoV- 2 vaccine.